Lower extremity lymphedema update: pathophysiology, diagnosis, and treatment guidelines - Kerchner, Katherine; Fleischer, Anne; Yosipovitch, Gil (Journal of the American Academy of Dermatology, 2008)
Lower extremity lymphedema is an important medical issue which causes morbidity and is frequently seen by dermatologists. The subject has not been adequately addressed in dermatologic literature for many years. Primary lymphedema is caused by an inherent malfunction of the lymph-carrying channel, in which no direct outside cause can be found. Secondary lymphedema is caused by an outside force, such as tumors, scar tissue after radiation, or removal of lymph nodes, which results in dysfunction of the lymph-carrying channels. Treatment is based on rerouting the lymph fluid through remaining functional lymph vessels. This is accomplished through elevation, exercises, compression garments/devices, manual lymph drainage, and treatment is combined with good skin care practices.